2020
DOI: 10.1002/jmv.26409
|View full text |Cite
|
Sign up to set email alerts
|

The role of DBP gene polymorphisms in the prevalence of new coronavirus disease 2019 infection and mortality rate

Abstract: Since December 2019, coronavirus disease 2019 (COVID‐19), caused by severe acute respiratory syndrome coronavirus 2, has given rise to emerging respiratory infections with pandemic diffusion. The vitamin D binding protein (DBP) with emphasis on its regulation of total and free vitamin D metabolite levels participate in various clinical conditions. The main goal of this study was to evaluate if there was any association between the DBP gene polymorphism at rs7041 and rs4588 loci and the prevalence of COVID‐19 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 36 publications
0
36
0
2
Order By: Relevance
“…Age may be another important factor to consider as a significant interaction between age and vitamin D deficiency was observed for associations with COVID-19 severity in one study ( 215 ). Other important considerations include genetic influences, with significant associations between polymorphisms in the vitamin D-binding protein and the prevalence and mortality due to COVID-19 reported ( 261 ). How ethnicity affects our capacity to make vitamin D after exposure to sun exposure (or UVB radiation) is a further important factor, which has been discussed ( 121 , 262 ).…”
Section: Vitamin D and Covid-19mentioning
confidence: 99%
“…Age may be another important factor to consider as a significant interaction between age and vitamin D deficiency was observed for associations with COVID-19 severity in one study ( 215 ). Other important considerations include genetic influences, with significant associations between polymorphisms in the vitamin D-binding protein and the prevalence and mortality due to COVID-19 reported ( 261 ). How ethnicity affects our capacity to make vitamin D after exposure to sun exposure (or UVB radiation) is a further important factor, which has been discussed ( 121 , 262 ).…”
Section: Vitamin D and Covid-19mentioning
confidence: 99%
“…The relationship between these GWAS associations and race was not explored in this study. A recent paper suggested that these SNPs in the DBP gene, specifically in the rs7041 locus, correlated with the prevalence (GT genotype: r=0.73, p=0.02; TT genotype: r=−0.62, p=0.04) and mortality (GT genotype: r=0.87, p=0.01; TT genotype: r=−0.66, p=0.04) rates of COVID-19 among all investigated populations [ 6 ]. More in detail, subjects with a TT genotype had a higher COVID-19 susceptibility in China, Japan, Nigeria, and Kenya.…”
Section: To the Editormentioning
confidence: 99%
“…A recent study has showed the rs7041 locus to be associated with increased risk of COVID-19 infection and mortality [19] . Therefore, the association of the genetic polymorphisms of DBP and COVID-19 may depend on the modulatory pleiotropic effects of the bioavailable vitamin D levels.…”
mentioning
confidence: 99%